Precision Measurement of the (e++e−) Flux in Primary Cosmic Rays from 0.5 GeV to 1 TeV with the Alpha Magnetic Spectrometer on the International Space Station - Aguilar M. (American Physical Society, 2025)
We present a measurement of the cosmic ray (e++e-) flux in the range 0.5 GeV to 1 TeV based on the analysis of 10.6 million (e++e-) events collected by AMS. The statistics and the resolution of AMS provide a precision measurement of the flux. The flux is smooth and reveals new and distinct information. Above 30.2 GeV, the flux can be described by a single power law with a spectral index γ=-3.170±0.008(stat+syst)±0.008(energyscale).